Issues in Requirement Engineering of Object-Oriented Information Systems: A Review - Lee, Sai Peck (Malaysian Journal of Computer Science, 2017)
Information Systems (ISs) engineering, which covers requirements engineering and design engineering, has been oriented to adopting object-oriented concepts in its theoretical foundation as a basis for development tools to achieve higher quality and productivity with lower cost. In this paper, we present a review of the various problematic issues specifically in requirements engineering of objectoriented ISs engineering and we mention some existing research attempts to deal with such issues. Some of these problematic issues are related to the lack of expressiveness of the conceptual model used in most analysis methods and the rigidity of the Computer Aided Software Engineering (CASE) tools supporting these methods. We also discuss some important issues in design engineering which are closely linked to those in requirements engineering, such as the integration of analysis and design tools to p